Designing and Implementing a New Seniors Services Coordinator Role for Low-Income Housing: A Qualitative Study. Issue 1 (2nd January 2023) - Sheppard, Christine L.; Hemphill, Julia; Austen, Andrea; Hitzig, Sander L.
ABSTRACT: Older adults living in social housing are disproportionally impacted by poverty, social isolation, and chronic health conditions that negatively impact their housing stability. In response, service coordination models of care that provide proactive case management have seen widespread adoption across low-income seniors housing communities. We examined the design and implementation of a new "seniors services coordinator" (SSC) role that was introduced by a social housing provider in Toronto, Canada. We conducted qualitative focus groups with tenants (n = 16), housing and policy staff (n = 16), and government-funded care coordinators (n = 16) to understand how the new SSC position formed relationships with tenants, assessed tenant needs and coordinated services, and built partnerships with government-funded system navigators. Since staff were assigned to specific buildings and had smaller caseloads, stakeholders felt that the SSC would be well positioned to build relationships of trust with tenants. Histories of mistrust, boundaries and time management, role conflicts, and system-level barriers, however, made it difficult for SSCs to fully carry out their role. Our findings highlight several design and implementation considerations that may impact the success of tenant-facing support staff such as SSCs, which can serve as a roadmap for other housing providers looking to implement similar initiatives.